Semiconductor nanostructures towards electronic and opto‐electronic device applications V. Issue 12 (December 2015) - Moreels, Iwan; André, Pascal; Climente, Juan I.; Reece, Peter; Ribierre, Jean‐Charles
Abstract: In 2015, the E‐MRS spring meeting in Lille hosted the fifth installment of the bi‐annual symposium " Semiconductor nanostructures towards electronic and opto‐electronic device applications ". Organized for the first time in 2007, the symposium brought together researchers from different fields working on nanostructured materials and their application in opto‐electronics and photonics. Several sessions discussed the latest developments in the growth of CuInS2, InP, and group‐IV nanocrystals, III–V quantum dots and nanowires, and 2D materials such as graphene, MoS2 and BN. These were accompanied by presentations dedicated to the characterization of the electronic, optical and plasmonic properties, and charge transport in nanostructured films. New applications of these materials were also discussed, with an emphasis on nanostructured organic and inorganic transistors and LEDs, lasers, detectors and sensors. Selected papers of the symposium are published in this special issue. Next to the contributed articles and proceedings, a feature article by Pavesi et al. highlights recent progress on silicon nanocrystals for optical communications [DOI: 10.1002/pssa.201532528].